Occupational characteristics and disability-free survival after retirement age: an exploratory analysis from the ASPREE study - Alif, Sheikh M.; Benke, Geza P.; Ronaldson, Kathlyn J.; Walker-Bone, Karen; Woods, Robyn L.; Tran, Cammie; Beilin, Lawrence J.; Tonkin, Andrew M.; Owen, Alice J.; McNeil, John J. (Frontiers in Public Health, 2023)
Background Certain occupational characteristics have been linked with poor health and reduced longevity. However, the association between occupational characteristics and survival free of disability in a post-retirement age group, has not been investigated. Methods We investigated outcomes in 12,215 healthy older Australian adults in the Aspirin in Reducing Events in the Elderly (ASPREE) and ASPREE Longitudinal Study of Older Adults (ALSOP) sub-study. The ISCO-88 major occupational groups, settings and activity levels were assigned based on free text job descriptions. The Finnish Job Exposure Matrix was used to assign occupational characteristics to their three longest held jobs. The primary endpoint, disability-free survival, was defined as a composite measure of death, dementia or persistent physical disability. The endpoint of all-cause mortality was analysed separately. Because of multiple exploratory analyses only those associations with a 2-sided p-value less than 0.005 were considered statistically significant. Cox proportional hazard models were used to calculate adjusted hazard ratios. Results Having worked in an ‘elementary’ occupation was associated with a reduction in disability-free survival. A specific impact on disability-free survival was observed amongst those whose work had involved high accident risk, and adverse social climate. No significant relationship was identified with those previously exposed to sedentary work, vigorous physical activity, work primarily outdoors or a range of other occupational characteristics. All-cause mortality was not increased amongst any of the occupational groups. Conclusions This exploratory study found a reduction in survival free of disability amongst people who worked in ‘elementary’ occupations, with specific risks associated with occupations involving high accident risks and adverse social climate.